PENGARUH UKURAN ORGANISASI DAN KETERLIBATAN PENGUNA TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI DAN PT XYZ - Alcianno Ghobadi Gani (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThis study aims to determine how much influence the size of the organization and user involvement on the performance of the accounting information system at PT XYZ. By using this type of research causal research. With qualitative analysis, data obtained by questionnaire, Likert scale, population of research 392 employees. The sample collection method is saturated sampling, and with an error rate of 5% using SPSS 26.0, the results of the hypothesis test of Organizational Size (X1) have a positive effect on Accounting Information System Performance (Y). where the t-count value is 2.333 > t-table 1.960. This shows that the higher the level of Organizational Size, the System Performance Hypothesis test results of User Involvement in System Development (X2) have a positive effect on Accounting Information System Performance (Y). Where the t-count value is 2.297 > t-table 1.960. This shows that the higher the level of user involvement in system development, the better the accounting information system performance Keywords: Organizational Size, User Involvement, Accounting Information System